Estudo da influência da frequência no comportamento à fadiga do aço inoxidável austenítico AISI – 316 - Alves Júnior, Isaú de Souza (2023)
The development of components and structures using austenitic stainless steels due to their properties is a current reality. Due to their metastable structure, austenitics undergo martensitic transformation under cyclic loading (mechanical loads), which produce changes in the properties of the alloys. In this scenario, parts and structural systems under cyclic loads must have a fatigue life assessment base of the highest reliability, since fatigue failure suspends services and productions that affect the economy and produce safety risks. That said, the present study aims to analyze the impact of frequency on the fatigue behavior of austenitic stainless steel 316. The fatigue behavior was analyzed and compared at the loading frequency of 10 and 30 Hz. The characterization was performed through chemical analysis, optical and electron microscopy, and microhardness. The analyzes showed that there was an improvement in fatigue resistance when the steel was subjected to a cyclic stress frequency of 10 Hz compared to the frequency from 30 Hz. In addition, there was a longer cyclic loading time for nucleation in the lower frequency condition. The morphological aspects of the fracture surfaces of the investigated fatigue test specimens showed no difference in the region of nucleation or rupture, but showed differences in the dimension of the size of striations in the region of fatigue propagation. The crack growth rates (da/dN), obtained by spacing the fatigue striations, did not show significant differences for the da/dN curves. Given the above, it is believed that the differences shown are a consequence of the volume of martensite formed. Lower frequency, greater accumulation of plastic deformations, greater density of formation of deformation bands and, consequently, more formation of α'-martensite that favors greater resistance to fatigue.